BcsTx3 is a founder of a novel sea anemone toxin family of potassium channel blocker. (23rd August 2013) - Orts, Diego J. B.; Moran, Yehu; Cologna, Camila T.; Peigneur, Steve; Madio, Bruno; Praher, Daniela; Quinton, Loic; De, Edwin; Bicudo, José E. P. W.; Tytgat, Jan; de, José C.
<x xml:space="preserve">Abstract</x> Sea anemone venoms have become a rich source of peptide toxins which are invaluable tools for studying the structure and functions of ion channels. In this work, BcsTx3, a toxin found in the venom of a Bunodosoma caissarum (population captured at the Saint Peter and Saint Paul Archipelago, Brazil) was purified and biochemically and pharmacologically characterized. The pharmacological effects were studied on 12 different subtypes of voltage‐gated potassium channels (KV1.1–KV1.6; KV2.1; KV3.1; KV4.2; KV4.3; hERG and Shaker IR) and three cloned voltage‐gated sodium channel isoforms (NaV1.2, NaV1.4 and BgNaV1.1) expressed in Xenopus laevis oocytes. BcsTx3 shows a high affinity for Drosophila Shaker IR channels over rKv1.2, hKv1.3 and rKv1.6, and is not active on NaV channels. Biochemical characterization reveals that BcsTx3 is a 50 amino acid peptide crosslinked by four disulfide bridges, and sequence comparison allowed BcsTx3 to be classified as a novel type of sea anemone toxin acting on KV channels. Moreover, putative toxins homologous to BcsTx3 from two additional actiniarian species suggest an ancient origin of this newly discovered toxin family.